2022
DOI: 10.3390/jof8111230
|View full text |Cite
|
Sign up to set email alerts
|

Geo-Distribution Patterns of Soil Fungal Community of Pennisetum flaccidum in Tibet

Abstract: Pennisetum flaccidum can be used as a pioneer species for the restoration of degraded grasslands and as a high-quality forage for local yak and sheep in alpine regions. The geographical distribution pattern of soil fungal community can modify that of P. flaccidum. A field survey along 32 sampling sites was conducted to explore the geo-distribution patterns of soil fungal community of P. flaccidum in Tibet. Soil fungal species, phylogenetic and function diversity generally had a closer correlation with longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…on the Changbai Mountain. However, Zhang et al (2022) found that both the Chao1 and Shannon index of soil fungi decreased significantly from 2,785 m a.s.l. to 4,578 m, and the climate and soil properties had opposite effects on them in Tibetan Plateau.…”
Section: Changes In Soil Fungal Alpha Diversity With Elevationmentioning
confidence: 90%
See 2 more Smart Citations
“…on the Changbai Mountain. However, Zhang et al (2022) found that both the Chao1 and Shannon index of soil fungi decreased significantly from 2,785 m a.s.l. to 4,578 m, and the climate and soil properties had opposite effects on them in Tibetan Plateau.…”
Section: Changes In Soil Fungal Alpha Diversity With Elevationmentioning
confidence: 90%
“…Mountains have attracted increasing curiosity of ecologists because of their high sensitivity to global climate change (Frey et al, 2016). Elevational gradients in the high mountains are often characterized by dramatic changes in the abiotic and biotic factors within short geographical distances (Rime et al, 2016;Donhauser and Frey, 2018;Adamczyk et al, 2019;Zhang et al, 2021), including vegetation, soil physicochemical properties, precipitation, temperature and illumination (Shen et al, 2013;Lin et al, 2017;Zhang et al, 2022), which may lead to significant changes in soil microorganisms within short distance. For example, soil bacterial community diversity varied significantly with elevation, while soil fungal community diversity did not change across an elevational gradient of 400 m (Yu et al, 2019), but both the soil fungal and bacterial community diversities changed significantly with elevation across an elevational gradient of 1,500 m in the Tibetan Plateau (Han et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grasslands, as an important vegetation type in global ecosystems, are key resources for high-quality development of livestock industry and an important place for wildlife protection Zha et al, 2022;Han et al, 2022a;Wang and Fu, 2023). Alpine grasslands are important sections of global grasslands, and may be the most sensitive and fragile grassland types to global change (Zhang et al, 2015(Zhang et al, , 2022Fu and Sun, 2022). Alpine meadows and alpine steppes on the Qinghai-Tibet Plateau are not only two of the most typical alpine grasslands on the world, but also the grassland types closest to the sky on the earth (Zhang et al, 2015;Zong and Fu, 2021;Han et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…The ANPP and plant diversity of alpine grasslands are survival basis for maintaining yaks and other specific plateau grazing livestock and wild animals, which can ensure the livelihood of Tibetan people's on the Qinghai-Tibet Plateau Wang et al, 2022). Alpine grasslands of the Qinghai-Tibet Plateau are not only the typical regions with asymmetric warming among elevations (Qin et al, 2009;Du et al, 2019), but also the perfect areas to trace alterations in ANPP and biodiversity under external disturbance conditions (Trisos et al, 2020;Tian and Fu, 2022;Zhang et al, 2022). However, as we refer to the best knowledge, only one study has tried to explore the effects of asymmetric warming among elevations on plant species and phylogenetic composition in alpine grasslands on the Tibetan Plateau (Wang et al, 2021b) and no reports have investigated the impacts of asymmetric warming among elevations on ANPP and plant α-diversity in alpine grasslands of the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%